2023
DOI: 10.1021/envhealth.3c00030
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Adolescence Exposure to Industrial Air Pollution with Cancer in Young Adults

Abstract: There is substantial public concern about the health risks of proximity to petrochemical industries. In the Haifa Bay Area (HBA), which contains Israel’s densest industrial area, these concerns have been strengthened by elevated cancer mortality rates since the late 1960s. We studied the association between adolescent exposure to industrial air pollution in the HBA and adult-onset cancer. This is a historical cohort study. The study population comprised 2,187,317 subjects, using the Israeli medical corps data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Incidental MPs are unintentional emissions from human activities, such as coal combustion fly ashes, vehicle exhausts, etc. ,, Compared with natural and engineered particles, assessment of health risks associated with incidental particles is more complex due to the presence of associated pollutants including heavy metals, black carbon, organic matter, etc. Especially in industrial and roadside areas, the high exposure rate would bring in a greater risk to human health. The MPs can take part in the biogeochemical cycle of Fe, causing a widespread and long-term impact to the ecosystems and human health . Since the compositions, properties, and environmental fates of particles are source-dependent, a feasible tracing method for MPs is urgently needed for their risk assessment and biogeochemical cycle studies. , …”
Section: Introductionmentioning
confidence: 99%
“…Incidental MPs are unintentional emissions from human activities, such as coal combustion fly ashes, vehicle exhausts, etc. ,, Compared with natural and engineered particles, assessment of health risks associated with incidental particles is more complex due to the presence of associated pollutants including heavy metals, black carbon, organic matter, etc. Especially in industrial and roadside areas, the high exposure rate would bring in a greater risk to human health. The MPs can take part in the biogeochemical cycle of Fe, causing a widespread and long-term impact to the ecosystems and human health . Since the compositions, properties, and environmental fates of particles are source-dependent, a feasible tracing method for MPs is urgently needed for their risk assessment and biogeochemical cycle studies. , …”
Section: Introductionmentioning
confidence: 99%
“…Fine particulate matter (PM 2.5 , particles with aerodynamic diameter less than 2.5 μm) pollution seriously threatens human health. Ultrafine particles (UFPs, particles with aerodynamic diameter less than 0.1 μm) are particularly important, as they may be able to translocate across the respiratory epithelium and other biological barriers to translocate in the human body via the circulatory system. Black carbon (or soot) is a frequent component of PM 2.5 , which exists ubiquitously in the atmosphere. It may be able to invade into the human body through the respiratory system or cross other biological barriers due to their nanoscale size and then accumulate in intracorporeal organs. It has been documented that long-term exposure to black carbon particles may cause a range of health risks, including respiratory diseases, cardiovascular diseases, and neurodevelopmental disorders. Notably, earlier studies have detected black carbon particles in different human organs, including human lung, healthy children urine, and the fetal side of human placenta. Regarding the human brain, some human and animal experiments have suggested that the ambient PM 2.5 species may invade the brain, resulting in the upregulation of inflammatory cytokines and disorder of the central nervous system (CNS). , However, evidence is still insufficient to unravel the exact exposure pathways of PM 2.5 species entering the human brain and their related toxicological mechanisms.…”
Section: Introductionmentioning
confidence: 99%